Succession of Maize (Zea mays L.) with some winter crops 1 – the effects on weed density and species - Sadalla, Hussain Ahmad; Mala.Galalay, Ali; Kakarash, Sakar Asaad.; Guznay, Jamal Borhan.; Gharib.Haji, Omar (Sulaimani Journal for Pure and Applied Sciences, 2017)
During the years 2011 and 2012 (two fall seasons and two winter), this study was conducted at Grdarash Research Station at Erbil, the capital city of the Kurdistan Region of Iraq, to study the population and species of weeds associated with wheat, canola, broad bean, peas and in a fallow plot. These crops were planted in R.C.B.D (randomized complete block design), with three replications during both winter seasons. Maize was planted during the fall seasons succeeded by winter crops. The kind of weed species and density were determined and counted with each winter and fall maize crop plantations during the four growing seasons. The results showed great differences in total weed density among winter crops. The lowest number of both narrow and broad leaf weeds was found in the wheat crop in the two winter seasons. In 2010-2011, the numbers were 15.7 and 86.6 respectively, while in 2011-2012 were 5.7 and 38.6 respectively. We can notice that the total number of both broad and narrow leaf weeds in the winter seasons of 2010-2011 was 167.9 and 756.3 respectively, while the numbers of weeds declined in 2011-2012 to 82.8 respectively 447.1. The lowest number of the narrow and broad leaf weeds in the fall season of 2011 was found in that stage of the experiment when wheat was followed by maize. The numbers were 38.3 and 32.7 respectively. As for the fall season of 2012, the lowest number was 21.7 respectively 14.3 for narrow and broad leaves.
Keywords: Succession; maize; weed density